Requirements management using IBM Rational RequisitePro - Zielczynski, Peter (IBM Press/Pearson plc, 2008)
Utilizing a start-to-finish sample project, requirements expert Peter Zielczynski introduces an organized, best-practice approach to managing requirements and shows how to implement every step with RequisitePro. You’ll walk through planning, eliciting, and clarifying stakeholder requirements; building use cases and other key project documents; managing changing requirements; transforming requirements into designs; and much more. Every stage of the process is illuminated with examples, realistic artifacts, and practical solutions.